2021
DOI: 10.5194/acp-2021-710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The diurnal and seasonal variability of ice nucleating particles at the High Altitude Station Jungfraujoch (3580 m a.s.l.), Switzerland

Abstract: Abstract. Cloud radiative properties, cloud lifetime, and precipitation initiation are strongly influenced by the cloud phase. Between ~ 235 and 273 K, ice nucleating particles (INPs) are responsible for the initial phase transition from the liquid to the ice phase in cloud hydrometeors. This study analyzes immersion-mode INP concentrations measured at 243 K at the High Altitude Research Station Jungfraujoch (3580 m a.s.l.) between February 2020 and January 2021, thereby presenting the longest continuous, high… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Data availability. The data presented in this publication are available at the following DOI: https://doi.org/10.3929/ethz-b-000548529 (Brunner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Data availability. The data presented in this publication are available at the following DOI: https://doi.org/10.3929/ethz-b-000548529 (Brunner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the influence of the PBL on Jungfraujoch is largest in summer and smallest in winter (Collaud Coen et al, 2011;Griffith et al, 2014). Hence, if samples are not explicitly selected for FT conditions, the majority of them will have at least some PBL influence, in particular during summer (Brunner et al, 2021b). Therefore, the concentration of INP −10 on filters not selected for FT conditions occasionally exceeded that of filters selected for FT conditions, in particular during summer (Fig.…”
Section: Comparison With Other Studies In the Swiss Alpsmentioning
confidence: 99%
“…6 in Lacher et al, 2018) as well as little seasonal variation. Later, continuous measurements by Brunner et al (2021b) found the monthly median of INP −30 in the FT background to peak in April and to be lowest in December. Brunner et al (2021a, b) found that most INP −30 at Jungfraujoch occurred during Saharan dust intrusions, by far exceeding any background concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral dust makes by far the largest contribution to INP activated at around -30 °C at Jungfraujoch (Larcher et al, 2018(Larcher et al, , 120 2021Brunner et al, 2021aBrunner et al, , 2021b. Most INP in airborne mineral dust are probably K-feldspars, some of which are already activated at temperatures above -10 °C (Boose et al, 2016;Harrison et al, 2019).…”
Section: Effect Of Saharan Dust Intrusionsmentioning
confidence: 99%
“…Generally, the influence of the PBL on Jungfraujoch is largest in summer and smallest in winter (Collaud Coen et al, 2011;Griffith et al, 2014). Hence, if samples are not explicitly selected for FT conditions, the majority of them will have at least some PBL influence, in particular during summer (Brunner et al, 2021b). Therefore, concentration of INP-10 on filters not https://doi.org/10.5194/acp-2021-879 Preprint.…”
Section: Comparison With Other Studies In the Swiss Alpsmentioning
confidence: 99%